Promotion of entrepreneurship development by art and design by pedagogy - Nebessayeva, Zhanar; Bekbolatova, Kuralay; Mussakulov, Kussan; Zhanbirshiyev, Sultanbek; Tulepov, Lesbek (Opción, 2019)
This paper discusses how art and design pedagogy can further entrepreneurship in societal, economic and educational contexts, so that students may thrive in a world full of complexity and flux. The author touches on some of the methodologies inherent in art and design pedagogy for teaching creativity and innovation and provides a broader overview of how the values and attitudes can further the current concepts of innovation and entrepreneurship and their societal and economic contexts. The paper highlights how the values, attributes and attitudes associated with art and design pedagogy translate into the economic focus of most current entrepreneurship thinking.